2017
DOI: 10.1371/journal.pone.0175874
|View full text |Cite
|
Sign up to set email alerts
|

5α-reductase 1 mRNA levels are positively correlated with TRAMP mouse prostate most severe lesion scores

Abstract: BackgroundThe contribution of 5α-reductase 1 and 5α-reductase 2 to prostate cancer development and progression is not clearly understood. TRAMP mice are a common prostate cancer model, in which 5α-reductase 1 and 5α-reductase 2 expression levels, along with prostate lesions scores, have not been investigated at different time points to further understand prostate carcinogenesis.Method/Principal findingsTo this end, 8-, 12-, 16-, and 20-week-old male C57BL/6TRAMP x FVB mice prostate most severe and most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Previous research has reported that SRD5A1 is highly expressed in prostate cancer (PC) ( 15 , 19 , 20 ), breast cancer ( 21 , 22 ), non-small cell lung cancer ( 23 ), and liver cancer ( 24 ). The upregulation of SRD5A1 promotes the formation and development of prostate intraepithelial neoplasia in vivo ( 25 ). Dutasteride, an inhibitor of SRD5A1/2 ( 26 ), which prevents T to DHT conversion, performs key functions in PC cell viability and proliferation ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that SRD5A1 is highly expressed in prostate cancer (PC) ( 15 , 19 , 20 ), breast cancer ( 21 , 22 ), non-small cell lung cancer ( 23 ), and liver cancer ( 24 ). The upregulation of SRD5A1 promotes the formation and development of prostate intraepithelial neoplasia in vivo ( 25 ). Dutasteride, an inhibitor of SRD5A1/2 ( 26 ), which prevents T to DHT conversion, performs key functions in PC cell viability and proliferation ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though 5α-reductase 1 has been found to increase in high grade versus low grade prostate cancer [ 54 , 55 ], this study is the first to report that tumor 5α-reductase 1 levels are positively correlated with adjusted prostate lesion score severity. Previously we found that prostate epithelium 5α-reductase 1 levels were positively correlated with adjusted prostate lesion score severity [30] . Collectively these may suggest that elevated 5α-reductase 1 levels are a characteristic of the increased malignant potential of tumors with higher prostate lesion scores.…”
Section: Discussionmentioning
confidence: 83%
“…The expression levels of Ki-67 and AR protein, apoptotic DNA fragmentation were quantified using IHC; and 5α-reductase 1 and 5α-reductase 2 mRNA were quantified using ISH in formalin-fixed, paraffin-embedded prostate tissue sections of AIN–93 G control, Pre-Finasteride, Post-Finasteride, Pre-Dutasteride, and Post-Dutasteride (n = 5) treated male TRAMP mice with GU weight < 1 gram; and AIN–93 G control, Pre-Finasteride, Post-Finasteride (n = 4), Pre-Dutasteride (n = 2), and Post-Dutasteride (n = 4) treated male TRAMP mice with GU weight > 1 gram. Biomarker assays and quantification in prostate epithelium, hyperplasia and tumor were performed as described previously [30] . Thresholds for positivity were defined so that they matched what was seen visually.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major sites of distribution of SRD5A in the human tissues are both in the reproductive organs (where the isoform SRD5A2 is prevalent) and in non-reproductive tissues, such as liver and skin, in which isoform SRD5A1 is the most commonly present [18,30]. In experimental animal models, it has been observed that the up-regulation of SRD5A1 promotes the formation and development of rat prostate intraepithelial neoplasia in vivo [31].…”
Section: Sex Steroid Hormones (Androgens)mentioning
confidence: 99%